Taxa de evasão e impacto financeiro na realidade da UNIFAL-MG - Gonçalves, Ira De Lizandra (2018)
The main objective of this work is to measure and analyze the graduation rate of undergraduate courses at the Federal University of Alfenas (UNIFAL-MG) and show the financial impact of the number of students evaded in the university budget. The study has as a representative universe 3522 students who escaped from their courses in the period from 2013 to 2016. To support this work, some conceptual validities about the evasion of upper-level students were reviewed. Data collection was done through bibliographic research, documentary research, quantitative research and qualitative research. The most relevant results obtained from documental research indicate that more than 50% of the dropout occurred mainly in the first year of the course. The researches of Tinto (1975, 1988) and Moraes and Theóphilo (2005) prove the same thing. The courses with the highest evasion rate, both using the evaded / entering ratio, and the "Lobo Institute", are Physics Degree (53.80% and 28.44%), Mathematics Degree (56.94% and 28.38 %) and Chemical Licenciatura (55.09% and 25.54%), all offered in the night shift. The overall result of the research showed an average dropout rate of university undergraduate courses of around 12% in the analyzed period. This rate is in accordance with the researches of Silva Filho et al. (2007) and Hipólito (2015). The numbers of the financial impact on the university budget, considering a universe of 3222 evaders, from 2013 to 2016, are very high, causing UNIFAL-MG to stop receiving more than R$ 71.000.000,00 via Budget Matrix for Other Costs and Capital (OCC Matrix). The institution also invested in Student Assistance for evaders from 2013 to 2016, about R$ 5.000.000,00.